Activated carbon/metal-organic framework nanocomposite: Preparation and photocatalytic dye degradation mathematical modeling from wastewater by least squares support vector machine. (1st March 2019) - Mahmoodi, Niyaz Mohammad; Abdi, Jafar; Taghizadeh, Mohsen; Taghizadeh, Ali; Hayati, Bagher; Shekarchi, Ali Akbar; Vossoughi, Manouchehr
Abstract: Herein, Kiwi peel activated carbon (AC), Materials Institute Lavoisier (MIL-88B (Fe), and AC/MIL-88B (Fe) composite were synthesized and used as catalysts to degrade Reactive Red 198. The material properties were analyzed by the FTIR, BET-BJH, XRD, FESEM, EDX, TGA, and UV–Vis/DRS. The BET surface area of AC, MIL-88B (Fe) and AC/MIL-88B (Fe) was 1113.3, 150.7, and 199.4 m 2 /g, respectively. The band gap values (Eg ) estimated by Tauc plot method, were obtained 5.06, 4.19 and 3.79 eV for AC, MIL-88B (Fe) and AC/MIL-88B (Fe), respectively. The results indicated that the AC/MIL-88B (Fe) composite had higher photocatalytic activity (99%) than that of pure AC (79%) and MIL-88B (Fe) catalysts (87%). The decolorization kinetic was matched well with the second-order model. Moreover, the data were modeled using least squares support vector machine which optimized with Cuckoo optimization algorithm. The optimal parameters were found 0.837 and 3.49e+02 based on σ 2 and γ values, respectively. The mean square error (MSE) and correlation coefficient (R 2 ) values were obtained 3.97 and 0.948. Therefore, the attained data, materials characterization and prediction of modeling validate the composite form of MIL-88B(Fe) with new AC, had better photocatalytic activity in comparison with the individual form. Graphical abstract: Image 1 Highlights: Activated carbon/metal-organic framework nanocomposite photocatalyst was prepared. Dye degradation mathematical modeling from wastewater was done. Surface area of AC, MIL-88B and AC/MIL-88B was 1113.3, 150.7, and 199.4 m 2 /g. The photocatalytic decolorization kinetics followed the second-order kinetic model. Least squares support vector machine with Cuckoo algorithm modeled dye degradation.